BODY TEMPERATURE MANAGEMENT IN PERIOPERATIVE AND INTENSIVE CARE: CLINICAL STRATEGIES FOR IMPROVING PATIENT OUTCOMES - Marta Nowocień; Karolina Witek; Joanna Kaźmierczak; Anna Mandecka; Kornela Kotucha-Cyl; Weronika Komala; Natalia Guzik; Joanna Gerlach; Dorota Plechawska (International Journal of Innovative Technologies in Social Science, 2025)
In perioperative and intensive care unit settings, body temperature management represents a fundamental aspect of patient supervision, profoundly influencing the efficacy of therapeutic interventions, the risk of complications, and overall patient prognosis. This study explores thermoregulatory mechanisms, the effects of temperature deviations, methods for controlled temperature modulation, while also addressing associated economic, sociological and ethical considerations. Based on the interpretation of available scientific evidence, it has been demonstrated that unmeasured temperature fluctuations constitute a fundamental challenge in the context of intensive care unit management and perioperative care, with their complications representing a critical factor in maintaining homeostasis. This work addresses the issue of technical temperature monitoring, the importance of an individualized approach to each clinical case, as well as the role of state-of-the-art technologies and their perception by patients and their relatives in life-threatening situations. Concurrently, it examines the expenditures associated with the use of cutting-edge technologies as a limiting factor in the widespread adoption of such procedures, potentially leading to inequalities in access to care and necessitating further economic considerations. The findings indicate that effective monitoring of core body temperature represents not only a fundamental element of clinical patient care but also a critical life-saving technology at the threshold of life and death. This review underscores the urgent need for comprehensive standards in thermoregulation and highlights the limitations of current clinical algorithms. These gaps call for rigorous randomized studies to refine existing protocols and ensure their reliability and efficacy in high-risk settings.